BCR-ABL1 mediated miR-150 downregulation through MYC contributed to myeloid differentiation block and drug resistance in chronic myeloid leukemia - Srutova, Klara; Curik, Nikola; Burda, Pavel; Savvulidi, Filipp; Silvestri, Giovannino; Trotta, Rossana; Klamova, Hana; Pecherkova, Pavla; Sovova, Zofie; Koblihova, Jitka; Stopka, Tomas; Perrotti, Danilo; et al. (Haematologica, 2018)
The fusion oncoprotein BCR-ABL1 exhibits aberrant tyrosine kinase activity and it has been proposed that it deregulates signaling networks involving both transcription factors and non-coding microRNAs that result in chronic myeloid leukemia (CML). Previously, microRNA expression profiling showed deregulated expression of miR-150 and miR-155 in CML. In this study, we placed these findings into the broader context of the MYC/miR-150/MYB/miR-155/PU.1 oncogenic network. We propose that up-regulated MYC and miR-155 in CD34+ leukemic stem and progenitor cells, in concert with BCR-ABL1, impair the molecular mechanisms of myeloid differentiation associated with low miR-150 and PU.1 levels. We revealed that MYC directly occupied the -11.7 kb and -0.35 kb regulatory regions in the MIR150 gene. MYC occupancy was markedly increased through BCR-ABL1 activity, causing inhibition of MIR150 gene expression in CML CD34+ and CD34- cells. Furthermore, we found an association between reduced miR-150 levels in CML blast cells and their resistance to tyrosine kinase inhibitors (TKIs). Although TKIs successfully disrupted BCR-ABL1 kinase activity in proliferating CML cells, this treatment did not efficiently target quiescent leukemic stem cells. The study presents new evidence regarding the MYC/miR-150/MYB/miR-155/PU.1 leukemic network established by aberrant BCR-ABL1 activity. The key connecting nodes of this network may serve as potential druggable targets to overcome resistance of CML stem and progenitor cells.
Keywords: senioři; bcr-abl fúzní proteiny; Gene Expression Regulation, Leukemic; nádorové buněčné linie; Cell Differentiation; Protein Kinase Inhibitors; geny myc; K562 Cells; mikro RNA; Fusion Proteins, bcr-abl; down regulace; Middle Aged; mužské pohlaví; Cell Proliferation; Adult; Cell Line, Tumor; buňky K562; MicroRNAs; Down-Regulation; chemorezistence; Genes, myc; ženské pohlaví; Humans; chronická myeloidní leukemie; Drug Resistance, Neoplasm; lidé středního věku; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; proliferace buněk; inhibitory proteinkinas; buněčná diferenciace; dospělí; HL-60 buňky; Neoplastic Stem Cells; Female; Aged; nádorové kmenové buňky; regulace genové exprese u leukemie; lidé; Male; HL-60 Cells